(untitled) (Global Journal of Human-Social Science, 2020)
Festivals impart entertainment in society people participate in socialization and festivals act as a mechanism to resolve the social tensions conflicts and social stress through participation of their members It provides a platform to express share and understand their ideas to others through interactions In a way it imparts societal glue because it offers people meaning and purpose for their lives and it gives definite values and meanings That s why people believe in religious religions offer ceremonies and festivals socialize their members with their values and ultimately festivals work an agency to control the behavior of people either imparting hope or creating by fear In fact religions rituals and festivals are practices required or expected of members of faith and usually honor the divine power or powers worshipped by believers the also remind adherents of their religious duties and responsibilities The objectives of this research article is to indentify how religion rituals and festivals are working as a mechanism to control social behavior how these functions in society to socialize the members and how they maintain the social order in such a diverse community like Nepal The diversities based on religions caste culture language etc was found in Nepal